2010
DOI: 10.1177/1934578x1000501131
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Biological Activity of Essential Oils from Piper Claussenianum (Piperaceae)

Abstract: Analyses of essential oils obtained from fresh and dried leaves and inflorescences of Piper clausenianum were performed using GC-FID, GC-MS and NMR techniques. Forty compounds were detected for these four oils with the total of identified constituents ranging from 88.7% for the dried inflorescences to 97.7% for the dried leaves. Sesquiterpenes were the main constituents in the volatile fraction from leaves with a high percentage of (E)-nerolidol (up to 83%). However, monoterpenes were identified in greater amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
2
25
0
1
Order By: Relevance
“…Nerolidol is a major component in several essential oils (Marques et al, ) that possesses various pharmacological properties, such as its antitumor, leishmanicidal, and antischistosomal activities (Arruda et al, ; Silva et al, ; Wattenberg, ). In addition, nerolidol is usually used in cosmetics as a fragrance (Yingngam and Brantner, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nerolidol is a major component in several essential oils (Marques et al, ) that possesses various pharmacological properties, such as its antitumor, leishmanicidal, and antischistosomal activities (Arruda et al, ; Silva et al, ; Wattenberg, ). In addition, nerolidol is usually used in cosmetics as a fragrance (Yingngam and Brantner, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, limited information is known in the literature regarding the tissue‐wise detailed systematic investigation of the essential oil yield and composition for the majority of Piper species. Essential oil from the reproductive parts has been investigated only for a few Piper species such as P. marginatum and P. claussenianum …”
Section: Resultsmentioning
confidence: 99%
“…Essential oil from the reproductive parts has been investigated only for a few Piper species such as P. marginatum and P. claussenianum. 37,38…”
Section: Essential Oil Yield Of P Betleoidesmentioning
confidence: 99%
“…Our group recently showed that the leaf essential oil from Piper claussenianum was able to inhibit the growth of L. amazonensis promastigotes with an IC 50 of 0.0038% (Marques et al, 2010). Trans-nerolidol is a major component of this essential oil.…”
Section: Anti-leishmanial Compoundsmentioning
confidence: 99%